2015
DOI: 10.1002/mnfr.201500605
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive effect of oleuropein in colitis‐associated colorectal cancer in c57bl/6 mice

Abstract: Oleuropein as a dietary supplementation could be a promising protective agent against colitis-associated CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
98
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 38 publications
3
98
0
Order By: Relevance
“…Nowadays, there is a strong evidence for the protective role of oleuropein against many types of cancer [22,23,24]. More specifically, Acquaviva et al, have recently demonstrated the antiproliferative effect of oleuropein in the androgen sensitive LNCaP and in the androgen insensitive DU145 prostate cancer cell line which are characterized by low and moderate tumorigenicity, respectively [25].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there is a strong evidence for the protective role of oleuropein against many types of cancer [22,23,24]. More specifically, Acquaviva et al, have recently demonstrated the antiproliferative effect of oleuropein in the androgen sensitive LNCaP and in the androgen insensitive DU145 prostate cancer cell line which are characterized by low and moderate tumorigenicity, respectively [25].…”
Section: Discussionmentioning
confidence: 99%
“…Further, it also significantly down regulated the CRC‐related pathways as Wnt/β‐catenin, signal transducer and activators of transcription (STAT)‐3, nuclear factor‐κB (NF‐κB), and phosphatidylinositol‐3‐kinase (P3IK)/Akt. Oleuropein suppressed the Th17 response by lowering Rorγt, T‐cell subsets, IL‐17, CD4, and IFN‐γ as well as IL‐17A and IFN‐γ expression in dextran sulfate sodium acute model (Giner, Recio, Ríos, Cerdá‐Nicolás, & Giner, ). The supplementation of oleuropein (125 mg/kg) in rats prevented the azoxymethane (AOM)‐induced preneoplastic lesions in different colon segments, reducing the severity of crypt dysplasia and DNA damage in peripheral leukocytes.…”
Section: Introductionmentioning
confidence: 99%
“…In the same animal model, OLE was found to downregulate the Th17 response, a key proinflammatory pathway activated in IBD [16]. These findings led us to hypothesize that OLE may have the potential to reverse chronic inflammation in UC.…”
Section: Introductionmentioning
confidence: 99%